Community Satisfaction Level With The Mass Vaccination In Kampung New Promission Village - Ayu Ramadhayani; Abd Halim; Yudi Prayoga (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The importance of community service is carried out as an effort to provide information and education to the community as an effort to help the central government and increase the role of universities as agents of change in community life through the Thematic Community Service Program/Developing Villages as well as assisting the village government in socializing to the community which is still minimal. information about vaccination in Kampung Baru Promise Village, Bilah Barat, Labuhanbatu. The method of implementing this service is carried out with a survey approach and outreach to 21 respondents which was carried out in the Village Hall of Kampung Baru Promise. The conclusion of this community service found that the approach through surveys to residents' homes was an alternative way to solve social problems related to vaccination. From the results of the socialization, it was concluded that all participants and the community who took part in this activity gave a good response and were very supportive. The intended village development service is to provide education and understanding to the community regarding the Level of Community Satisfaction with Vaccination. Assist the village government to accelerate the implementation of vaccination.